"Walking in the City": Performance of Strategies and Tactics in the 1985 Bus Accessibility Protests - Quinlan, Margaret M.; Bates, Benjamin R. (Disability Studies Quarterly, 2012)
In 1985, disability rights activists protested in Cleveland, Ohio. The story of this protest has been retold through performance to advocate making Cleveland more accessible to individuals with disabilities. This analysis explores the rhetorical performative work of the disability bus protest through interviews with a protest leader and examination of the intersections between these historical texts, and their retellings as appropriations oriented toward activist, educational, and aesthetic ends. Specifically, we emphasize the retellings and reenactments of these events as advocacy for altering public understandings of accessible transportation and of advocacy for individuals with and without disabilities. Using de Certeau's concepts of strategies, tactics, and walking in the city, we argue that the bus protest and its retelling recombine the rules and products that already exist in culture in a way that is influenced, but never wholly determined, by those rules and products. We offer implications for understanding activism by and on behalf of individuals with disabilities and for advocacy toward rewriting cities for accessibility. Key words: de Certeau, activism, The Dancing Wheels Company & School